Wear particles and ions from cemented and uncemented titanium‐based hip prostheses—A histological and chemical analysis of retrieval material. Issue 3 (23rd July 2014) - Grosse, Susann; Haugland, Hans Kristian; Lilleng, Peer; Ellison, Peter; Hallan, Geir; Høl, Paul Johan
Abstract: Wear debris‐induced inflammation is considered to be the main cause for periprosthetic osteolysis in total hip replacements (THR). The objective of this retrieval study was to examine the tissue reactions and exposure to metal ions and wear particles in periprosthetic tissues and blood samples from patients with titanium (Ti)‐based hip prostheses that were revised due to wear, osteolysis, and/or aseptic loosening. Semiquantitative, histological tissue evaluations in 30 THR‐patients revealed numerous wear debris‐loaded macrophages, inflammatory cells, and necrosis in both groups. Particle load was highest in tissues adjacent to loosened cemented Ti stems that contained mainly submicron zirconium (Zr) dioxide particles. Particles containing pure Ti and Ti alloy elements were most abundant in tissues near retrieved uncemented cups. Polyethylene particles were also detected, but accounted only for a small portion of the total particle number. The blood concentrations of Ti and Zr were highly elevated in cases with high abrasive wear and osteolysis. Our findings indicate that wear particles of different chemical composition induced similar inflammatory responses, which suggests that particle size and load might be more important than the wear particle composition in periprosthetic inflammation and osteolysis. © 2014 The Authors. Journal of Biomedical Materials Research Part B: Applied Biomaterials Published by Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B:709–717, 2015.